2019
DOI: 10.1667/rr15363.1
|View full text |Cite
|
Sign up to set email alerts
|

Use of Growth Factors and Other Cytokines for Treatment of Injuries During a Radiation Public Health Emergency

Abstract: Radiation oncology, military medicine, radiation protection a Speakers had the opportunity to review this meeting report prior to journal submission. b CBRNE ¼ chemical, biological, radiological, nuclear and explosive. 2 https://bit.ly/2ZJO9KH. 3 https://bit.ly/2U8OwdE 4 https://bit.ly/2XYai6h. 5 https://bit.ly/2OWDKpK. 6 https://bit.ly/2P28xl9. 7 https://bit.ly/2I8r7aI. 8 https://bit.ly/2uXqrfQ. 9 https://bit.ly/2I6Dq7r. 10 Where pre-publication data are discussed, the first initial and last name of the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 123 publications
0
20
0
Order By: Relevance
“…Epidermal growth factor (EGF) promotes epithelial and hematopoietic stem cells regeneration [ 259 ]. Bone marrow-derived hematopoietic stem cells (HSCs) express the EGF receptor in response to radiation and, in turn, EGF promotes HSCs regeneration in vivo.…”
Section: Medical Countermeasuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidermal growth factor (EGF) promotes epithelial and hematopoietic stem cells regeneration [ 259 ]. Bone marrow-derived hematopoietic stem cells (HSCs) express the EGF receptor in response to radiation and, in turn, EGF promotes HSCs regeneration in vivo.…”
Section: Medical Countermeasuresmentioning
confidence: 99%
“…Bone marrow-derived hematopoietic stem cells (HSCs) express the EGF receptor in response to radiation and, in turn, EGF promotes HSCs regeneration in vivo. Mechanistically, EGF reduced radiation-induced apoptosis through repression of PUMA proapoptotic protein, and EGF receptor signaling was needed for DNA repair and for HSCs regeneration [ 259 , 260 ]. rhNRG-1β is an EGF-like protein that maintained mitochondrial integrity and ATP production in irradiated cardiomyocytes and preserves cardiac function via the ErbB2-ERK-SIRT1 signaling pathway [ 261 ].…”
Section: Medical Countermeasuresmentioning
confidence: 99%
“…Various NHP studies over the last 25 years have shown the effect of leukocyte GFs on blood counts and survival. These GFs are indicated for treatment of ARS since they trigger expansion, growth and differentiation of radioresistant bone marrow stem cells to generate the various hematopoietic lineages, including neutrophils and megakaryocytes (24). In fact, the body naturally begins production of GFs and cytokines after irradiation (24), and radiation accident victims who experienced life-threatening radiation exposure (e.g., Chernobyl liquidators) exhibited spontaneous recovery of neutrophils and platelets (25).…”
Section: Natural History Of Diseasementioning
confidence: 99%
“…These GFs are indicated for treatment of ARS since they trigger expansion, growth and differentiation of radioresistant bone marrow stem cells to generate the various hematopoietic lineages, including neutrophils and megakaryocytes (24). In fact, the body naturally begins production of GFs and cytokines after irradiation (24), and radiation accident victims who experienced life-threatening radiation exposure (e.g., Chernobyl liquidators) exhibited spontaneous recovery of neutrophils and platelets (25). Similarly, accelerated platelet recovery in NHPs has been observed after administration of recombinant megakaryocyte growth and development factor (a truncated form of thrombopoietin) with and without G-CSF (26).…”
Section: Natural History Of Diseasementioning
confidence: 99%
“…). Further and despite the common observation of clinical efficacy, the use of these recombinants to treat heavily irradiated individuals does not by any means guarantee a survival benefit (DiCarlo et al 2019). The complexity of systemic injury due to such intense IR exposures often leads to multi-organ failure and, thus, is beyond the therapeutic capacity of these recombinants to salvage individuals with such clinical conditions.…”
mentioning
confidence: 99%